1986
DOI: 10.1007/bf02141494
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of retinal microcirculation in retinal vessel occlusion before and after treatment

Abstract: Blood flow, arterial velocity, and vascular diameter were measured in patients with retinal vessel occlusion before and after treatment, especially after light coagulation. The mean values in the patient group showed significantly reduced blood flow and velocity compared to the normal group. The mean group difference before and after therapy revealed that while there is an increase in blood flow after treatment, the normal value is not reached. Individual patient values indicated both increased and decreased b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Combining measurements of blood flow (Cunha-Vaz and Lima, 1978;Oswald et al, 1983;Riva et al, 1972;Sato et al, 2006;Vilser et al, 1986) and of arterial oxygen saturation (Beach et al, 1999;Delori et al, 1981;Hickham et al, 1963;Laing et al, 1975;Schweitzer et al, 1999Schweitzer et al, , 1995 the supply of the tissue with oxygen can be calculated. Additionally, the arterio-venous difference of the oxygen saturation enables an estimation of the oxygen consumption in the tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Combining measurements of blood flow (Cunha-Vaz and Lima, 1978;Oswald et al, 1983;Riva et al, 1972;Sato et al, 2006;Vilser et al, 1986) and of arterial oxygen saturation (Beach et al, 1999;Delori et al, 1981;Hickham et al, 1963;Laing et al, 1975;Schweitzer et al, 1999Schweitzer et al, , 1995 the supply of the tissue with oxygen can be calculated. Additionally, the arterio-venous difference of the oxygen saturation enables an estimation of the oxygen consumption in the tissue.…”
Section: Introductionmentioning
confidence: 99%
“…(1996) suggested that circulation velocity increases in the areas with laser burns 3–9 months after laser treatment. Vilser et al. (1986) observed an increase in RBF after laser treatment but RBF did not reach normal values.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, Bertram and coworkers [22] observed that circulation velocity increases in the areas with laser burns 3-9 months after laser photocoagulation (PC). Similarly Vilser et al [23] showed an increase in retinal blood flow (RBF) after PC but RBF did not reach normal values. According to Arvas et al [24] study by Heidelberg retinal flowmetry (HRF) if the laser burns were not extensive; grade 2 and 3a burns do not damage the internal capillary plexus and this has even further positive effect on blood flow values.…”
mentioning
confidence: 90%